Bridging Educational Equity Through ICT Learning: Lessons from Learning Behaviour and Challenges in Welcoming ICT of Children at a Rural Area - Adi Suryani; Soedarso; Moh. Saifulloh; Marsudi (Future Science)
This study aims to explore challenges and learning behavior of children at Desa Balerejo, Kecamatan Pangungrejo, Blitar, in welcoming ICT introduction program. Education is the heart of community development. The creation of learning community and its’ development is sustained by community education, including its’ young generation education. Children are the future of the community. They will be the next leaders and their community developers. Thus, providing sufficient education is vital for assuring certain community existence and development sustainability. However, in reality, not all children can pursue equal education. Education in some remote areas is still left behind. Consequently, children in rural areas, are frequently suffering from educational disparities. The data are collected through direct observation during the community service program, through our roles as community service program providers as well as the instructors. The study is the result of our reflection, what happens in the field and what can be improved for future empowerment programs. The study indicates that there are several substantial factors determine and pose challenges for the effectiveness of ICT education for children at rural area. The first factor is culture and social context. Submissive and collectivism cultural orientation may affect the children’s behavior. The second aspect is the teaching approaches and learning psychology of children. Teaching method and materials should be adapted to the children, what they like and how they may learn best. The last factor is relating the nature of the empowerment program, which should be executed collaboratively and simultaneously with other programs.